Peran Penyuluh dan Persepsi Petani terhadap Tingkat Adopsi Teknologi Pengelolaan Tanaman Terpadu (PTT) Padi di Kecamatan Lumbir Kabupaten Banyumas - Dian Adha Sari; Totok Agung Dwi Haryanto; Edi Santoso; Dyah Susanti; Ardiansyah Ardiansyah (Universitas Batanghari Jambi, 2026)
This study aimed to analyze the effects of the role of agricultural extension workers and farmers' perceptions on the level of ICM technology adoption in lowland rice farming. This study employed a quantitative survey method involving 98 farmers selected through Proportional Simple Random Sampling. The collected data were analyzed using multiple linear regression. The results indicated that both the role of agricultural extension workers and farmers' perceptions had a positive and significant effect, both individually and simultaneously, on the adoption level of ICM technology (p < 0.05). The coefficient of determination (R²) was 0.585, indicating that 58.5% of the variation in the adoption level of ICM technology could be explained by these two variables, while the remaining 41.5% was influenced by other factors not examined in this study. These findings emphasize the importance of strengthening the role of agricultural extension workers and improving farmers' positive perceptions to promote wider adoption of ICM technology.